2019
DOI: 10.1029/2018wr024422
|View full text |Cite
|
Sign up to set email alerts
|

Defensive Investment in Municipal Water Hardness Reduction

Abstract: Household willingness to pay (WTP) for reductions in water hardness was estimated using a defensive investment framework. Using total dissolved solids data observed in municipal water supplies in combination with product-by-store level point-of-sale scanner data on consumable water softening product sales, we reveal preference estimates of WTP for water hardness reduction and quality control. Using instrumental variable regressions, we show that household marginal WTP increases as the observed total dissolved … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…The difference in the length of contact disaffection decreases the level of water hardness in the filtration and absorption processes. Filtration or filtering is the initial process in water treatment which is carried out physically to separate particles in water (Farah et al, 2019). In this filtration process, there is a process of separating solids from the solution to remove very fine suspended particles, where the solution is passed through a porous medium or porous material.…”
Section: Resultsmentioning
confidence: 99%
“…The difference in the length of contact disaffection decreases the level of water hardness in the filtration and absorption processes. Filtration or filtering is the initial process in water treatment which is carried out physically to separate particles in water (Farah et al, 2019). In this filtration process, there is a process of separating solids from the solution to remove very fine suspended particles, where the solution is passed through a porous medium or porous material.…”
Section: Resultsmentioning
confidence: 99%
“…Up to now, several technologies, including chemical precipitation, ion exchange, and membrane separation, have been developed for water softening. 6,7 Despite their high effectiveness, tackling the challenges associated with chemical input, concentrated brine handling, and material regeneration is still on the way. 8 Recently, electrochemical-induced precipitation has been proposed as a sustainable alternative, avoiding the addition of reagents and the discharge of concentrated brine.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Long-term use of water with high hardness will not only cause bad corrosion and scaling but also induce possible adverse health effects. Therefore, point-of-entry water-softening devices are highly desirable in many households, as the maximum permissible tap-water hardness is still high (e.g., 450 mg/L for the national standard in China). Up to now, several technologies, including chemical precipitation, ion exchange, and membrane separation, have been developed for water softening. , Despite their high effectiveness, tackling the challenges associated with chemical input, concentrated brine handling, and material regeneration is still on the way . Recently, electrochemical-induced precipitation has been proposed as a sustainable alternative, avoiding the addition of reagents and the discharge of concentrated brine.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies investigated the effect of nanofiltration membrane type (TW30, NE70 and NE90) and feed pressure on ion rejection and reported that the TW30 membrane at a pressure of 10 bar produced the highest removal of calcium, magnesium and chloride, with 96.1, 98.7 and 90.3%, respectively [11]. Cavitation is a physical phenomenon consisting of the formation, growth and subsequent collapse of cavities that occur in small time intervals, releasing large levels of energy[ [12] [13]. The hydrodynamic cavitation performance is affected by various parameters such as inlet pressure, cavitation device, location of the cavitation device, flow rate, diameter and material of the pipe, etc.…”
Section: Introductionmentioning
confidence: 99%